EKSISTENSI PASAR KINANTI DI ERA DIGITAL: PERAN MEDIA SOSIAL DALAM MEMPERTAHANKAN PASAR TRADISIONAL - Hera Febrianti; Widie Dwitami Sukendari; Isti Mudrikatun Azzahra (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2026)
Digital transformation poses both challenges and opportunities for the sustainability of community-based traditional markets. This study examines how social capital, cultural practices, and digital media contribute to the sustainability of Pasar Kinanti in the digital era. Using a qualitative case study approach, data were collected through in-depth interviews with ten key informants, supported by digital documentation and literature review. Data were analyzed using the interactive model of Miles and Huberman. The findings show that Pasar Kinanti’s sustainability is shaped by the synergy of social capital (bonding, bridging, and linking), local cultural practices, and digital media strategies for representation and visibility. The market functions not only as an economic space but also as a social and cultural arena that strengthens community identity through traditional arts and intergenerational participation. Digital media expands public reach and reinforces the market’s image as an alternative cultural space. However, structural challenges persist, including unequal role distribution, dependence on social media algorithms, and risks of cultural commodification. This study proposes a conceptual model of community-based traditional market sustainability integrating social capital, cultural practices, and the digital cultural economy, contributing to scholarship on traditional markets and community-based development in local contexts.